1997
DOI: 10.1128/mcb.17.4.2076
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Human γ-Globin Gene Expression in Adult Mice Carrying a Transgene of Deletion-Type Hereditary Persistence of Fetal Hemoglobin

Abstract: Persistent expression of the ␥-globin genes in adults with deletion types of hereditary persistence of fetal hemoglobin (HPFH) is thought to be mediated by enhancer-like effects of DNA sequences at the 3 breakpoints of the deletions. A transgenic mouse model of deletion-type HPFH was generated by using a DNA fragment containing both human ␥-globin genes and HPFH-2 breakpoint DNA sequences linked to the core sequences of the locus control region (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
10

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 38 publications
2
19
0
10
Order By: Relevance
“…The main impetus behind this study had been the elucidation of the molecular basis of HPFH as a result of large deletions in the human β-globin locus, which often include the Enh and F elements. Two models have been proposed to account for the generation of the HPFH phenotypes; the deletion of silencer elements in the Aγ to δ-gene region (17), and/or the juxtaposition of downstream enhancers (18)(19)(20)(21). The novel data described here and in previous studies (25)(26)(27)59) suggest that elements located in the Aγ to δ intergenic region contribute to specific regulation of the individual globin genes at different developmental stages.…”
Section: O V E M B E R -D E C E M B E R 2 0 0 9 T W O S I L E N C E Rmentioning
confidence: 67%
See 1 more Smart Citation
“…The main impetus behind this study had been the elucidation of the molecular basis of HPFH as a result of large deletions in the human β-globin locus, which often include the Enh and F elements. Two models have been proposed to account for the generation of the HPFH phenotypes; the deletion of silencer elements in the Aγ to δ-gene region (17), and/or the juxtaposition of downstream enhancers (18)(19)(20)(21). The novel data described here and in previous studies (25)(26)(27)59) suggest that elements located in the Aγ to δ intergenic region contribute to specific regulation of the individual globin genes at different developmental stages.…”
Section: O V E M B E R -D E C E M B E R 2 0 0 9 T W O S I L E N C E Rmentioning
confidence: 67%
“…It also has been suggested (18), without being mutually exclusive, that the juxtaposition of distal sequences located downstream of the 3′ breakpoint of these deletions with enhancer-like function also may be involved in persistent γ-globin expression. The validity of the latter hypothesis for the HPFH deletions has been documented conclusively (experimentally) in vivo by us (19,20) and by others (21) with the identification and functional characterization of a series of HPFH enhancers (19)(20)(21). A similar mechanism may be operating in the HPFH-5 and HPFH Kenya deletions via the juxtaposition of the 3′ β-globin enhancer to the proximity of the fetal genes (1,16).…”
Section: Persistent Fetal γ-Globin Expression In Adult Transgenic Micmentioning
confidence: 68%
“…The formation of Hb Bart's would further decrease the already limited pool of binding partners for excess a-globin chains, resulting in increased a-chain precipitation and proerythrocyte destruction. Secondly, previous studies have also demonstrated that hybrid mouse/human HbF, as well as Hb Bart's, have decreased oxygen affinity (Arcasoy et al, 1997;Shear et al, 1998), which, in combination, would diminish the ability of surviving RBC in these mice to efficiently deliver oxygen. In summary, human c-globin can fully correct the heterozygous Hbb th)3 /+ mouse model of b-thalassaemia intermedia in a dose-dependent manner and in association with an increased survival of RBC-containing hybrid mouse/human HbF.…”
Section: Discussionmentioning
confidence: 99%
“…We can propose two possible explanations for the failure of c-globin to rescue the lethal phenotype in Hbb th)3 /Hbb th)3 mice. First, previous studies have demonstrated that c-globin has a strong propensity for forming Hb Bart's (c 4 homotetramers) in transgenic mice (Arcasoy et al, 1997). Although the underlying mechanisms for this propensity are unclear, it suggests a basic inefficiency of hybrid mouse a-globin/human c-globin heterotetramer formation.…”
Section: Discussionmentioning
confidence: 99%
“…The first sequence located immediately downstream to the 3 0 breakpoint of the HPFH-1and HPFH-2 deletion was shown to act as enhancers in transient transfection assays and in transgenic mice. This region was marked by an erythroid specific DNase I hypersensitive site extending from 1.1 to 1.4 kb 3 0 to the HPFH-1 breakpoint [1][2][3][4]. A second region with enhancer activity in a transient system lies between the breakpoints of HPFH-6 and Chinese G g( A gdb) 0 -thalassemia [4,5].…”
Section: Introductionmentioning
confidence: 99%